Performance analysis of multi-institutional data sharing in the Clouds4Coordination system. (February 2017) - Petri, Ioan; Rana, Omer F.; Beach, Tom; Rezgui, Yacine
Highlights: Use of a federated, multi-Cloud environment within a construction/architecture consortium. Use of the CometCloud system to implement a multi-cloud environment, enabling partners within a collaborative projects to aggregate their computational infrastructure. Implementation of an Application Programming Interface (API) to enable such Cloud federation. Realising a use case in construction/architecture using the Building Information Model across a multi-Cloud environment. Performance analysis of the multi-Cloud use in the context of the use case, by measuring an "aggregate time to complete" metric. Graphical abstract: Abstract: Cloud computing is used extensively in Architecture/ Engineering/ Construction projects for storing data and running simulations on building models (e.g. energy efficiency/environmental impact). With the emergence of multi-Clouds it has become possible to link such systems and create a distributed cloud environment. A multi-Cloud environment enables each organisation involved in a collaborative project to maintain its own computational infrastructure/ system (with the associated data), and not have to migrate to a single cloud environment. Such infrastructure becomes efficacious when multiple individuals and organisations work collaboratively, enabling each individual/ organisation to select a computational infrastructure that most closely matches its requirements. We describe the "Clouds-for-Coordination" system, and provide a use case to demonstrate how such a system can be used in practice. A performance analysis is carried out to demonstrate how effective such a multi-Cloud system can be, reporting "aggregated-time-to-complete" metric over a number of different scenarios.